General method of rapid Smith/Birnstiel mapping adds for gap closure in shotgun microbial genome sequencing projects: application to Pseudomonas putida KT2440 - Weinel, Christian (Oxford University Press, 2001)
A physical mapping strategy has been developed to verify and accelerate the assembly and gap closure phase of a microbial genome shotgun-sequencing project. The protocol was worked out during the ongoing Pseudomonas putida KT2440 genome project. A macro-restriction map was constructed by linking probe hybridisation of SwaI- or I-CeuI-restricted chromosomes to serve as a backbone for the quick quality control of sequence and contig assemblies. The library of PCR-generated SwaI linking probes was derived from the sequence assembly after 3- and 6-fold genome coverage. In order to support gap closure in regions with ambiguous assemblies such as the repetitive sequence of the seven ribosomal operons, high-resolution Smith/Birnstiel maps were generated by Southern hybridisation of pulsed-field gel electrophoresis-separated rare-cutter complete/frequent-cutter partial digestions with rare-cutter fragment end probes. Overall 1.5 Mb of the 6.1 Mb P.putida KT2440 genome has been subjected to high-resolution physical mapping in order to align assemblies generated from shotgun sequencing.